Meningkatkan Minat Belajar Materi Keliling dan Luas Bangun Datar Penerapan Model Guided Discovery dengan Eksperimen untuk Kelas IV SDN Gayamsari 02 - Hayuningtyas Putri; Choirul Huda; Loli Adi Gunawan (Journal on Education, 2024)
This research aims to explore the effectiveness of implementing the Guided Discovery Model using experiments to enhance students' interest in learning the concepts of perimeter and area of plane figures in the fourth-grade class at SDN Gayamsari 02. This approach attempts to integrate a more active and student-centered learning approach to improve students' understanding of fundamental mathematical concepts. The research method employed is classroom action research involving active participation of both teachers and students in every stage of implementation. Data were collected through observations, interviews, and surveys on learning interest. The findings indicate a significant increase in students' interest in learning after implementing the Guided Discovery Model with experiments. There is a notable improvement in students' understanding of the concepts of perimeter and area of plane figures. This discovery supports the effectiveness of the Guided Discovery Model in stimulating learning interest and understanding mathematical concepts at the elementary school level, providing a foundation for a more interactive and relevant learning approach tailored to students' needs in mastering complex mathematical materials. The practical implications of this research highlight the importance of using active exploration-based learning methods and involving students to enhance their learning outcomes.